Utrudnienia w komunikowaniu się w korporacjach transnarodowych - Kanafa-Chmielewska, Dorota (Difficulties with communication in multinational corporations, 2006)
Working for multinational corporation has now become commonplace. At the contact point of different cultures, some misunderstandings may occur derived from communication difficulties. Do people of divergent cultures vary so much? Research presented in the paper hints a negative answer to this question. In particular, if one takes into consideration such fundamental aspect of interpersonal communication as facial expression o f emotions. Studies of cross-cultural psychology are finding more and more evidence that communication among people representing different cultures and nations can be easier than one has thought so far.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 356-363